(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This study explores the morphological formation of phytonyms—lexical units derived from plant names—in the Uzbek epic Alpomish. It investigates how morphological processes such as suffixation and derivation contribute to building vivid botanical images that serve as metaphors and similes within the oral poetic structure. The article analyzes suffix forms like -day, -dayin, and others originating from dialectal variation, highlighting their grammatical and stylistic roles in developing phytonyms. By combining linguistic, folkloric, and dialectological perspectives, the work reveals how morphological creativity supports semantic depth and aesthetic richness in Uzbek epic traditions, reinforcing cultural values and oral heritage.